Commerce, finances et crises financieres - K. Michael Fingerand; Ludger Schuknecht (World Trade Organization (WTO), 1999)
Cette étude de l'OMC explique les liens fondamentaux entre le commerce et le secteur financier, et les relations d'interdépendance entre les crises financières et le commerce. – – This study by the WTO explains the basic links between trade and the financial sector, and how financial crises are interrelated with trade.
Keywords: 330